Impact of low energy electron beam on black pepper (Piper nigrum L.) microbial reduction, quality parameters, and antioxidant activity - Abdul Basit M. Gaba; Mohamed A. Hassan; Ashraf A. Abd El-Tawab; Mohamed A. Abdelmonem; Mohamed K. Morsy (AIMS Agriculture and Food, 2022)
Low energy electron beam (e-beam) has the ability to decontaminate or reduce bioburden and enhance the food product's safety with minimal quality loss. The current study aimed to evaluate the efficacy of e-beam on natural microbiota and quality changes in black peppercorns. The black pepper was exposed to e-beam at doses from 6–18 kGy. The microbial quality, physicochemical attributes, total phenolic compounds, and antioxidant activity were evaluated. Results demonstrated the microbial population in black pepper decreased with increasing e-beam treatment doses. Significant inactivation of Total Plate Count (TPC), yeasts, and molds were observed at dose 6 kGy by 2.3, 0.7, and 1.3 log CFU g−1, respectively, while at 18 kGy the reduction level was 6, 2.9, and 4.4 log CFU g−1, respectively. Similarly, 18 kGy of e-beam yielded a reduction of 3.3 and 3.1 log CFU g−1 of Salmonella Typhimurium and coliform bacteria, respectively. A significant difference (p < 0.05) was noted between doses 12, 15, and 18 kGy on Bacillus cereus and Clostridium perfringens in black pepper. During e-beam doses, the values L*, a* and b* of black peppercorn were not noticeably altered up to 18 kGy dose. No significant (p > 0.05) difference in moisture, volatile oil, and piperine content upon (6–18 kGy) treatments in comparison to the control. A slight difference in the bioactive compound, retaining > 90% of total phenolic compounds and antioxidant activity. Results revealed that e-beam doses ≥ 18 kGy were influential for inactivating natural microbes and foodborne pathogens without compromising the physicochemical properties and antioxidant activity of black peppercorns.